2010
DOI: 10.1352/1944-7558-115.1.19
|View full text |Cite
|
Sign up to set email alerts
|

National Cost Efficiency of Supported Employees With Intellectual Disabilities: 2002 to 2007

Abstract: The cost efficiency of supported employees with intellectual disabilities who were served by vocational rehabilitation agencies throughout the United State from 2002 to 2007 was explored. Findings indicate that, on average, supported employees with intellectual disabilities were cost-efficient from the taxpayers' perspective regardless of whether they had secondary disabilities. In addition, no changes in cost efficiency were found during the period investigated. The data, however, did demonstrate considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Yet, as pointed out in a recent review of research by Cimera (2012), extensive research has been conducted since the 1980s that has found people with disabilities in general and people with IDD specifically benefited more financially by working in their community than working in sheltered workshops. These findings have been confirmed in more recent studies, some of which replicated the cost-accounting methodologies used in earlier research (Cimera, 2009;Cimera, 2010b;Cimera 2012;Cimera & Burgess, 2011).…”
Section: The Economics Of Worksupporting
confidence: 68%
See 2 more Smart Citations
“…Yet, as pointed out in a recent review of research by Cimera (2012), extensive research has been conducted since the 1980s that has found people with disabilities in general and people with IDD specifically benefited more financially by working in their community than working in sheltered workshops. These findings have been confirmed in more recent studies, some of which replicated the cost-accounting methodologies used in earlier research (Cimera, 2009;Cimera, 2010b;Cimera 2012;Cimera & Burgess, 2011).…”
Section: The Economics Of Worksupporting
confidence: 68%
“…As a tax-payer investment, studies from the 1980s and 1990s suggest the costefficiency of support employment in the community is mixed (Hill & Wehman, 1983;McCaughrin, Ellis, Rusch, & Heal, 1993;Rusch, Conley, & McCaughrin, 1993;Tines, Rusch, McCaughrin, & Conley, 1990;Wehman et al, 1985). More recent research found that context matters greatly in that the cost-efficiency for tax payers depends on the state in which employment services are provided (Cimera, 2010a(Cimera, , 2010b. In addition, the phase of support for the supported employees working in the community matters.…”
Section: The Economics Of Workmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2006, every state had supported employment programs, with total spending (federal and state) of $709 million, accounting for 21 percent of all individuals participating in education, leisure, and work-related programs o¤ered during the day (Braddock, Hemp, and Rizzolo, 2008). A recent national study …nds that on average across states, $1 spent on supported employment returns $1.21, with the savings coming primarily in reduced expenditures on alternative day services (Cimera, 2010). For the SC program we study, McInnes et al (2010) …nd that the job coaching services for the average placement cost roughly $7100 but save $10,000 in avoided shelter workshop payments.…”
Section: Supported Employment and Job Coachingmentioning
confidence: 99%
“…A multitude of economic evaluations of SE programs, comparing these to regular vocational training programs etc., has been conducted in the U.S. (Cimera, 1998(Cimera, , 2010a(Cimera, , 2012Conley et al, 1989;Hill & Wehman, 1983;Hill et al, 1987;Latimer, 2001;Rogers et al, 1995). An early European such study, for Wales, is the one by Beyer and Kilsby (1998).…”
Section: Introductionmentioning
confidence: 99%